A fundamental investigation of the Caro's acid cyanide destruction process. (30th October 2015) - Hewitt, D. M.; Simons, A. M.; Breuer, P. L.
Abstract : Cyanide destruction by Caro's acid is a process commonly employed by gold operations to meet regulatory requirements and/or the International Cyanide Management Code compliance for weak acid dissociable (WAD) cyanide concentrations in cyanidation tails or waste water from such operations. Typically small-scale bench tests to evaluate and assess the suitability of the Caro's acid destruction process are conducted before implementation. Additionally, the experimental procedure used during these preliminary investigations may also differ from that implemented at the full scale. This paper presents the results from a fundamental investigation of the Caro's acid process to establish a more detailed understanding of the impact that the Caro's acid source, alkali used and experimental procedure has on the destruction of cyanide. In particular, it was found that the control of pH was important to avoid additional (greater than stoichiometry) cyanide and copper loss (most likely as copper(I) cyanide precipitation) at low pH and maximise WAD cyanide destruction. Residual peroxide in the preparation of Caro's acid has the potential for subsequent cyanide destruction and could be exploited.